2017
DOI: 10.1007/s10484-017-9355-3
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Cardiac Autonomic Control during a Stress Reactivity Assessment Among Primary Care Patients with Metabolic Syndrome

Abstract: Metabolic syndrome (MetS) comprises a constellation of metabolic abnormalities that substantially increase risk for chronic illnesses. Autonomic dysregulation is closely linked to MetS, and while pathophysiological models often address chronic stress exposure, none have examined how such physiological contributions operate situationally, in a clinical setting. We used ambulatory impedance cardiography to examine indicators of cardiac autonomic control (CAC) in a sample of 50 adult primary care patients with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Autonomic nervous system imbalance, or an increase in sympathetic activity coupled with a decrease in parasympathetic activity, has been associated with poorer physiological health outcomes including metabolic abnormalities (Licht et al, 2013) and cardiovascular disease risk factors (i.e., hypertension, diabetes) (Thayer et al, 2010b), as well as worse psychological outcomes, including anxiety (Friedman and Thayer, 1998), depression (Stone et al, 2020), and increased levels of daily stress (Mitchell et al, 2017). Due to its importance in health research, there have been several attempts to accurately measure cardiac autonomic balance and regulation over the years using various physiological measures.…”
Section: Autonomic Balance and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomic nervous system imbalance, or an increase in sympathetic activity coupled with a decrease in parasympathetic activity, has been associated with poorer physiological health outcomes including metabolic abnormalities (Licht et al, 2013) and cardiovascular disease risk factors (i.e., hypertension, diabetes) (Thayer et al, 2010b), as well as worse psychological outcomes, including anxiety (Friedman and Thayer, 1998), depression (Stone et al, 2020), and increased levels of daily stress (Mitchell et al, 2017). Due to its importance in health research, there have been several attempts to accurately measure cardiac autonomic balance and regulation over the years using various physiological measures.…”
Section: Autonomic Balance and Healthmentioning
confidence: 99%
“…CAB and CAR can be calculated using indices of parasympathetically mediated HRV (e.g., the root mean square of successive differences [RMSSD], HF-HRV) and impedance derived systolic time intervals (i.e., pre-ejection period [PEP]) as an index of sympathetic activity (Berntson et al, 2008;Williams et al, 2017). Both CAB and CAR have been used as indices of autonomic balance and activity in a myriad of studies, showing associations with affective responses (Kreibig et al, 2012), psychopathologies (Bylsma et al, 2015;Stone et al, 2020), stress (Gump et al, 2011;Mitchell et al, 2017), inflammatory markers (Singh et al, 2009;Alen et al, 2020), and physiological health (Berntson et al, 2008;Vrijkotte et al, 2015). For example, a history of myocardial infarctions and type 2 diabetes diagnoses are more likely to be linked to low levels of CAR and CAB, respectively (Berntson et al, 2008), while lower CAB has also been shown to be associated with increased levels of inflammatory cytokines such as interleukin-6 and tumor necrosis factor alpha (Alen et al, 2020).…”
Section: Autonomic Balance and Healthmentioning
confidence: 99%
“…As in the retrospective cases, these subjects had lower CAR scores prior to the MI, indicating that low CAR may be a prospective predictor as well. Subsequent work has supported the view that patterns of CAR and CAB, beyond simply the individual metrics of sympathetic and parasympathetic control, may be predicting of metabolic and cardiovascular disease (Licht et al, 2010(Licht et al, , 2013Mitchell et al, 2017). These results suggest that distinct patterns of autonomic control may be associated with distinct health dimensions.…”
Section: Car Vs Cab and Healthmentioning
confidence: 77%
“…Finally, the present experiments are limited to a particular population and paradigm: seated young women in good cardiac health working on a mental effort task for cash rewards. It would be valuable to compare PEP and RZ in other contexts where sympathetic cardiac activity is commonly assessed, such as paradigms using physical exercise, pharmacological blockades, and mental and physical stressors (e.g., Lackner et al, 2015;Meyer et al, 2016;Mitchell et al, 2017). To date, there's some evidence that RZ's similarity to PEP is general beyond mental effort, such as physical exertion (van Eijnatten et al, 2014;Wilde et al, 1981), Valsalva maneuvers (Meijer et al, 2010), and dobutamine infusion (van der Meer et al, 1999).…”
Section: Discussionmentioning
confidence: 99%